The effect of the nature of the adversative relations on the online processing of but-sentences - Tsilimos, Maria; Ozubko, Jason (East European Journal of Psycholinguistics, 2023)
The purpose of the study was to extend the knowledge about two different types of adversative relations. The study pertaining to the principles of the Connective Integration Model (Millis & Just, 1994) included two experiments to examine the effect of two types of but-sentences (type 1 and type 2) in connective and non-connective versions on reading comprehension and recall performance. Reading comprehension was measured by clause 2 reading times, response times to comprehension questions and answer accuracy, while recall performance was measured via probe recognition times and accuracy in probe answers. The results of Experiment 1 indicated that the connective versions led to faster clause 2 reading times, faster answer latencies and greater answer accuracy than did the non-connective versions. Experiment 1 also showed that the semantic constraints related to the two types of but-sentences had an impact on reading speed and comprehension, since it was found that type 1 but-sentences were associated with faster clause 2 reading times, answer latencies and higher answer accuracy than were type 2 but-sentences in the non-connective versions versus the connective versions, and that type 2 but-sentences were read faster than were type 1 but-sentences in the connective versions. The results of Experiment 2 only indicated greater accuracy in probe answers in the type 1 versus the type 2 but-sentences in the connective and non-connective versions.Data Availability StatementThe data analysis as well as the stimuli sentences underlying this article are available in the Open Science Framework repository, at https://osf.io/sc2e8/?view_only=ff1ac9ffb5ee4dddbfe0e6aba0322c2aThe experimental (anonymous) data cannot be stored in a repository since in the Consent letter, given prior to the experiments, the participants agreed that their data would be used only for the purposes of the current study and that in no way will identify them in any papers or reports written about the research. The participants also agreed that their data would be destroyed three months after the experiments.The study was preregistered on 13.03.23 prior to the conduct of the experiments in the Open Science Framework repository, at https://doi.org/10.17605/OSF.IO/CG6QTEthics and ConsentThis project has been reviewed by, and received ethics clearance through the Ethics Committee of the Faculty of Arts and Social Sciences at the University of Zurich.Disclosure StatementNo potential conflict of interest was reported by the authors.* Corresponding author: Maria Tsilimos, 0000-0002-5167-553X maria.tsilimos@uzh.ch